On the influence of the anodic porous transport layer on PEM electrolysis performance at high current densities. (28th February 2020) - Lickert, Thomas; Kiermaier, Maximilian L.; Bromberger, Kolja; Ghinaiya, Jagdishkumar; Metz, Sebastian; Fallisch, Arne; Smolinka, Tom
Abstract: In this study, the influence of the anodic porous transport layer (PTL) on the performance of a proton exchange membrane (PEM) electrolysis laboratory test cell was investigated up to a current density of 5 A*cm −2 . Operation parameters such as water volume flow rate (0.2–0.8 l*min −1 ), temperature (40–80 °C) and pressure (1–30 barg) have been varied to study their influence on the polarisation curve. Special attention has been paid to the appearance of mass transport losses (MTL) and their dependency on the operation parameters. Two stack designs that are commercially in use - one with and one without flow channels underneath the PTL - were tested and evaluated. Fundamental differences in performance have been observed between the two cell designs. Operation parameters only show impact on performance for the configuration without flow channels. Here, MTL were observed in several cases already for current densities around and above 1.0 A*cm −2 . An increase in pressure, temperature or water flow rate reduces MTL for these configurations. Highlights: Performances of electrolysers with and without flow field can differ significantly. Also temperature (T), pressure (p) and flow rate (Q) influence the performance. Performance of electrolysers without flow field benefit from increased T, p and Q. Porosities and particle/fiber diameters are not enough to characterise PTLs. Also in-plane and through-plane permeability are needed for proper characterisation.